2017
DOI: 10.4274/tjh.2016.0394
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of CD56 and CD117 Expressions at the Time of the Diagnosis in Multiple Myeloma Patientsple Myeloma Patients

Abstract: Objective:The purpose of this study is to investigate the relationship between the CD56 and CD117 expressions and the clinical and laboratory findings in multiple myeloma (MM) patients.Materials and Methods:Analyses of multiparametric flow cytometry data obtained from the diagnostic bone marrow aspirations of a total of 34 newly diagnosed MM patients were assessed retrospectively. CD56 and CD117 expressions of the patients were compared with their stages and clinical parameters. The staging was performed accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 31 publications
5
18
1
Order By: Relevance
“…A uniform protocol was also applied. Elevation in CD117 and CD56 levels reported by Pan et al ( 8 ) and Ceran et al ( 9 ) resulted from varying treatments, including chemotherapies and novel agents. The influence of different regimes and potential resulting bias was not accounted for.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…A uniform protocol was also applied. Elevation in CD117 and CD56 levels reported by Pan et al ( 8 ) and Ceran et al ( 9 ) resulted from varying treatments, including chemotherapies and novel agents. The influence of different regimes and potential resulting bias was not accounted for.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Pan et al ( 8 ) suggested that CD56 and CD117 expression has a potential prognostic impact and it may be associated with increased OS. Ceran et al ( 9 ) reported that CD56 and CD117 expression levels are lower in advanced stages of MM. Qiu et al ( 24 ) reported that OS and PFS in CD56+ patients with MM are increased compared with CD56- patients treated with lenalidomide or bortezomib-based therapies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations